Earthquake response analysis of the Hualien soil structure interaction system based on updated soil properties using forced vibration test data. - Choi, Jun-Seong (Earthquake engineering & structural dynamics.)
This paper presents results of the earthquake response analysis on a large scale seismic test (LSST) structure which was built at Hualien in Taiwan for an international cooperative research project. The analysis is carried out using a computer program which has been developed based on axisymmetric finite element method incorporating dynamic infinite elements for far field soil region and a substructured wave input technique. The non-linear behaviour of the soil medium is taken into account using an iterative equivalent linearization procedure. Two sets of the soil and structural properties, namely te unified and the FVT-correlated models, are utilized as the initial linear values. The unified model was provided by a group of experts in charge of the geotechnical experiments, and the correlated model was obtained through a system identification procedure using the forced vibration test (FVT) results by the present authors. Three components of ground accelerations are artificially generated through an averaging process of the Fourier amplitude spectra of the ground accelerations measured near the test structure, and they are used as the control input motions for the earthquake analysis. It has been found that the earthquake responses predicted using the generated control motions and with the FVT-correlated model as the initial linear properties in the equivalent linearization procedure compare very well with the observed responses.